2002
DOI: 10.1016/s0925-4773(03)00113-8
|View full text |Cite|
|
Sign up to set email alerts
|

Mouse Crossveinless-2 is the vertebrate homolog of a Drosophila extracellular regulator of BMP signaling

Abstract: The Dpp/BMP signaling pathway is highly conserved between vertebrates and invertebrates. The recent molecular characterization of the Drosophila crossveinless-2 (cv-2) mutation by Conley and colleagues introduced a novel regulatory step in the Dpp/BMP pathway (Development 127 (2000) 3945). The CV-2 protein is secreted and contains five cysteine-rich (CR) domains similar to those observed in the BMP antagonist Short gastrulation (Sog) of Drosophila and Chordin (Chd) of vertebrates. The mutant phenotype in Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…These weak DV patterning defects can be explained by the presence of other anti-BMP molecules acting together with Chordin. Examples include Noggin, Follistatin, Sizzled, and Crossveinless-2 (Smith and Harland, 1992;Hemmati-Brivanlou et al, 1994;Bachiller et al, 2000;Yabe et al, 2003;Martyn and Schulte-Merker, 2003;Coffinier et al, 2002;Dal-Pra et al, 2006;Rentzsch et al, 2006). Consistent with this idea, triple knockdown of noggin, follistatin, and chordin in amphibian embryo, indeed, resulted in a drastic deletion of dorsal structures (Khokha et al, 2005), which is never obtained by a single or double depletion of these genes.…”
Section: Chordin Ut006 Shows Various Degree Of Ventralized Phenotypementioning
confidence: 78%
“…These weak DV patterning defects can be explained by the presence of other anti-BMP molecules acting together with Chordin. Examples include Noggin, Follistatin, Sizzled, and Crossveinless-2 (Smith and Harland, 1992;Hemmati-Brivanlou et al, 1994;Bachiller et al, 2000;Yabe et al, 2003;Martyn and Schulte-Merker, 2003;Coffinier et al, 2002;Dal-Pra et al, 2006;Rentzsch et al, 2006). Consistent with this idea, triple knockdown of noggin, follistatin, and chordin in amphibian embryo, indeed, resulted in a drastic deletion of dorsal structures (Khokha et al, 2005), which is never obtained by a single or double depletion of these genes.…”
Section: Chordin Ut006 Shows Various Degree Of Ventralized Phenotypementioning
confidence: 78%
“…and M.B.O., unpublished). Vertebrate homologs of Cv2 can bind Bmps, and act variously as agonists or antagonists of Bmp signaling in different assays (Kamimura et al, 2004;Coffinier et al, 2002;Binnerts et al, 2004). It is not clear by what mechanism Cv2 promotes Bmp signaling during PCV formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported Cv2 expression in embryonic and adult mouse tissues as well as in ES cells (Coffinier et al, 2002;Moser et al, 2003).…”
Section: Temporal and Spatial Expression Of Cv2 During Embryogenesismentioning
confidence: 97%
“…At E12.5, the Cv2 -/-mice exhibit no remarkable gross defects and are found in a Mendelian ratio (see Table S1 in the supplementary material; M.I. and Y.S., unpublished), even though Cv2 is expressed in the rostral mesoderm and the caudal primitive streak during gastrulation (Coffinier et al, 2002).…”
Section: The Function Of Cv2 Is Not Essential For All Bmpdependent Emmentioning
confidence: 99%